The Auditor’s Responsibility is to Apply the Concept of Materiality in Accordance with the Standard (ISA.320) in Determining Analytical Audit Procedures to Reduce Audit Risks - Jaafar Abdulhussein Hilo Aljabi, (Technium Business and Management, 2024)
The research aims to clarify the auditor’s responsibility for applying the concept of materiality in accordance with the (ISA.320) standard in determining the analytical audit procedures represented by the process of assessing audit risks. To achieve the research aims, the descriptive analytical approach was used to deal with data collection and classification. The main study tool, represented by the questionnaire form, was used to collect data from the study sample, which was analyzed through the SPSS program. The questionnaire was distributed to a number of sample members, and the number was suitable for conducting statistical analysis, as it reached 45 questionnaires, of which 40 questionnaires were suitable for analysis. The most important conclusions were that there is a statistically significant effect of the auditor’s analytical procedures when applying the International Auditing Standard Materiality (ISA.320) in assessing audit risks. The study recommended the need for the Accounting and Auditing Council to take measures to verify the compliance of Iraqi audit offices with audit risk assessment procedures through the use of analytical procedures by the auditor in accordance with International Auditing Standard 320 Materiality